An Arabic translation of the research: A simulation- based curriculum to introduce key teamwork principles to medical students at Vanderbilt University in the USA (Journal of medical and pharmaceutical sciences, 2022)
The aim of translating this study is to clarify the importance of teamwork and the importance of introducing medical students to its principles, and to provide a mechanism for training them early before they reach the clinical training years where it will become difficult to modify their behavior, and this training should include unidisciplinary and multidisciplinary collaboration.Medical colleges always strive to raise the level of public health by focusing on making the patient safety the first goal for its graduates. However, cooperation between the members of the medical team and their understanding of each other roles is the cornerstone of patient safety, and the curricula do not explicitly include skills and behaviors required for the success of this cooperation.This study has been held at Vanderbilt University in the United States of America on a group of first- year medical students. The researchers used a training package that included the specific knowledge, skills, attitudes and behaviors required to work effectively as part of a team. The researchers presented these skills through training courses offered to junior medical students- over a period of four years- and for two weeks annually.The training course contained an introduction to the most important topics in modern health care, in cooperation with the Experimental Learning and Evaluation Center, the sample consisted of (420) evaluation forms, and the results showed that the evaluations of the training course were positive, as almost all questions had averages greater than 5 of 7 in all four years.It should be noted that the use of simulation is the best way to inculcate any behavior, knowledge or skill in students, as simulation offers us a way to bring students closer to the ground and prepare them for what they may face during their future career.Based on the results, I added a set of recommendations to activate the strategy of cooperative training and teamwork within the medical schools, and added some similar past studies, which I believe will benefit those who seek and wish to improve and develop the curriculum of medical schools.
Keywords: teamwork; communication; simulation; interpersonal skills; curriculum development; repetitions